1997
DOI: 10.21273/horttech.7.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Plant Water Status as an Index of Irrigation Need in Deciduous Fruit Trees

Abstract: To be useful for indicating plant water needs, any measure of plant stress should be closely related to some of the known short- and medium-term plant stress responses, such as stomatal closure and reduced rates of expansive growth. Midday stem water potential has proven to be a useful index of stress in a number of fruit tree species. Day-to-day fluctuations in stem water potential under well-irrigated conditions are well correlated with midday vapor-pressure deficit, and, hence, a nonstressed baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
117
2
30

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(154 citation statements)
references
References 0 publications
5
117
2
30
Order By: Relevance
“…A high correlation between W MD and W STEM was found in Mediterranean fruit woody plants, such as grapevine (Stevens et al, 1995;Williams and Araujo, 2002), though this may not hold true for other fruit trees of temperate environments, such as apple (Naor et al, 1995). Measurements of W PD on olive provided a good estimate of the soil moisture status within the orchard, being responsive to water applications in early stages of the experiment; however, also W STEM was reflective of the amount of water in the soil profile under the environmental and soil conditions of this study, being a sensitive indicator of water stress earlier than W MD (see Shackel et al, 1997). Experimental evidences suggest that W PD may come into equilibrium with the wettest portion of the soil in the plant's root zone (see Ameglio et al, 1999).…”
Section: Discussionmentioning
confidence: 79%
“…A high correlation between W MD and W STEM was found in Mediterranean fruit woody plants, such as grapevine (Stevens et al, 1995;Williams and Araujo, 2002), though this may not hold true for other fruit trees of temperate environments, such as apple (Naor et al, 1995). Measurements of W PD on olive provided a good estimate of the soil moisture status within the orchard, being responsive to water applications in early stages of the experiment; however, also W STEM was reflective of the amount of water in the soil profile under the environmental and soil conditions of this study, being a sensitive indicator of water stress earlier than W MD (see Shackel et al, 1997). Experimental evidences suggest that W PD may come into equilibrium with the wettest portion of the soil in the plant's root zone (see Ameglio et al, 1999).…”
Section: Discussionmentioning
confidence: 79%
“…Moreover, knowledge of the behaviour of these PBWSI is essential when their continuous and automatic registers are used for automatic irrigation scheduling (Moreno et al 1996, Shackel et al 1997, Goldhamer and Fereres 2004.…”
Section: Introductionmentioning
confidence: 99%
“…The most widely used approach for evaluating tree water status has been to determine leaf water potential (Ame´glio et al, 1999;Hsiao, 1990). However, Chone´et al (2001), Naor (2000) and Shackel et al (1997) showed that midday stem water potential (Y stem ) is a significant and more reliable plant water status indicator for scheduling the irrigation of woody crops. However, the main disadvantage of Y stem is the relatively cumbersome measurement procedure, the necessity of frequent trips to the field and a significant input of labour.…”
Section: Introductionmentioning
confidence: 99%
“…To correctly interpret the values of each plant-based water status indicator and their use for irrigation scheduling, it is necessary to develop baselines or reference relationships, which are obtained with their values in plants under nonlimiting soil water conditions versus the evaporative demand of the atmosphere Martin et al, 1990;Shackel et al, 1997).…”
Section: Introductionmentioning
confidence: 99%